Peran Kurikulum Merdeka dalam Meningkatkan Kualitas Pembelaran di SMAN 1 Taman Sidoarjo - Putri, Rizka Nadilla; Nurlaila, Ayu; Sari, Dewi Candra Kartika; Rahmawati, Diah; Webiatama, Falfa Dwika; Wulandari, Ayu; Nuphanudin, Nuphanudin (MASALIQ, 2024)
The aim of this research is to determine the extent to which the process of implementing Curriculum Management, especially the Independent Curriculum at SMAN 1 Taman Sidoarjo, has improved the educational process to be of higher quality and able to adapt to the K13 curriculum; The method used in this research is a qualitative method where a researcher goes directly into the field to interview sources face to face to obtain relevant results; The result of this research is to understand the transition process from the K13 curriculum to the Merdeka curriculum at SMAN 1 Taman Sidoarjo which requires further efforts to provide support and training to teachers and improve educational facilities and infrastructure at SMA Negeri 1 Taman - Sidoarjo so that it runs optimally. ; The implementation of the Independent Curriculum at SMAN 1 Taman Sidoarjo has achieved a fairly good level of success. Teachers are actively involved in developing relevant learning materials and supporting student development. However, despite progress, there are still challenges in implementing the Merdeka Curriculum at SMA Negeri 1 Taman - Sidoarjo, such as a lack of resources, inadequate teacher training, and resistance to change. This requires further efforts to provide support and training to teachers and improve educational facilities and infrastructure. SMA Negeri 1 Taman - Sidoarjo has succeeded in developing a curriculum that is responsive to student needs, including innovative and technology-based learning approaches. This development needs to be adopted by more schools to increase relevance to global and local needs. Carrying out P5 projects with the support of the entire school community is one way to enable students to play an active role in their learning. The independent study program supports comprehensive character and skills development.